"HISTOPATHOLOGY OF LIVER IN CATTLE SPONTANEOUSLY INFECTED WITH FASCIOLA HEPATICA AND FASCLOLA GLGANTICA IN IRAN" - J.Massoud; L.Vedadi (Tehran University of Medical Sciences, 1982)
A total of 1500 infected liver with F. hepatica and F. gigantica from slaughtered cattle in different parts of Iran were studied. Grossly the livers were usually irregular in shape, with prominent bile ducts on the visceral surface as grayish-white, firm-branching streaks. The atrophy of the left lobe due to fibrosis and ischemia were noticed. On the cut surface the main bile ducts wall consisted of hard fibrotic tissue with pipe-stem appearance and calcium deposition on the inner layer of the ducts in F.hepatica infection. In the livers infected with F.gigantica, grossly seemed to be of a more normal consistency with much less calcium deposition in the ducts. In histopathological changes there was evidence of different stages of parenchymal damages, varying from fresh burrow with young flukes inside to old and healed nodules due to migration of the young flukes. A large number of eosinophils, lymphocytes plasma cells, disintegration of hepatocytes and coagulation necrosis were seen. The thickening of the bile ducts wall and the intense fibrous tissue proliferation in the portal areas compressed the adjacent liver cells, causing pressure atrophy of the liver. In very chronic cases glandular hyperplasia of ducts wall which lined by columnar epithelial cells with vacuolated cytoplasm were marked. In some ducts compact aggregation of fibroblasts which gave a smooth appearance to the bile ducts wall were noticed. The monolobular fibrosis in both F.hepatica and F.gigantica infections were a typical feature.